Algol 68 Dialect Conversion -- a Syntactic Approach - Brailsford, David F.; Knott, R. D. (1976)
A syntax directed package for converting Revised Algol 68 programs into Algol 68-R form, (where possible) is being developed at Nottingham. The package makes use of J.M. Foster's Syntax Improving Device (SID) [1]. The experience gained has underlined the value of a syntactic approach to problems of this sort. A far wider range of constructs can be translated than would ever be possible by using ad hoc methods. In many respects the difficulties encountered are those of conventional compiler writing, but some intriguing new problems arise when, as in this case, the source language and target language differ relatively little in philosophy and appearance.